Tensile strength of CFRP with curvilinearly arranged carbon fiber along the principal stress direction fabricated by the electrodeposition resin molding. (April 2021) - Katagiri, Kazuaki; Honda, Shinya; Nakaya, Shota; Kimura, Takahiro; Yamaguchi, Shimpei; Sonomura, Hirosuke; Ozaki, Tomoatsu; Kawakita, Sonomi; Takemura, Mamoru; Sasaki, Katsuhiko
Abstract: To strengthen carbon fiber reinforced plastics (CFRPs), fiber placement along the principal stress directions have been studied as a promising approach. However, a method to sufficiently impregnate a resin between the curved carbon fibers has not established thus far, although arbitrary arrangement of carbon fibers is feasible using the automated fiber placement (AFP) machine. Previously, the authors had developed an electrodeposition resin molding method based on electrophoresis. In this method, the carbon fiber preforms sewn by the AFP machine is immersed in the electrodeposition solution containing polymers with epoxy groups, and optimal current is applied to impregnate resin between carbon fibers. In this study, we showed that a CFRP specimen could be fabricated with arranging the carbon fibers along the principal stress direction, resulting in approximately 10% higher tensile strength than that of the specimen with unidirectional carbon fibers.